Clima organizacional y gestión académica del docente de la Universidad Técnica “Luis Vargas Torres” de Esmeraldas sede Santo Domingo - Puyol-Cortez, Jorge Luis (Editorial Grupo AEA, 2022)
Organizational behavior is somewhat unpredictable due to the very different personalities of the individuals working in the same institution such as universities, being necessary a method to regulate behavior while complying with legal requirements established by the governing bodies of higher education. The objective of this article is to analyze the organizational behavior and the performance of the teachers of the Technical University Luis Vargas Torres of Esmeraldas, Santo Domingo Campus, in order to improve the efficiency with which the processes are carried out and to comply with the institutional objectives by establishing guidelines for the conduct of teachers. As for the methodology used, the bibliographic review method was chosen by searching for information through books, scientific and academic articles. In the discussion, deficiencies in the instability of organizational behavior are evidenced, thus affecting performance and the application of new practices in the institution. The results indicate that there is a direct relationship between leadership and organizational behavior in the educational environment leading to the conclusion that the implementation of actions to generate a positive organizational behavior in pedagogical management allows the creation of an environment with better communication, focus and performance improvement, which allows the growth of the establishment.